Islamic architecture discourse and development of a syllabus for facilitating critical dialogue in history of architecture - Hasnan, Liyana (2019)
Traditional lecture-based pedagogy has remained fundamentally unchanged. This is particularly true with the teaching of History of Architecture where trends of contents and education have not changed. The research finds that Islamic architecture's discourse is a complex subject with multiple narratives that are often swept under a metanarrative, positioned as the ‘other’ towards Western history. Passive learning of knowledge could lead learners to experience cultural alienation, detaching students from contemporary issues. The research argues for an in-depth inquiry into the syllabus design as a pedagogical tool towards critical learning of History of Architecture with a focus on Islamic architecture. The purpose of the research is to design a course syllabus that could facilitate dialogue in class. The research posits that developing the syllabus focusing on the contents of history and theory can facilitate critical learning among students, to identify multiple histories and narratives within Islamic architecture. The research uses an integrated case study and grounded theory methodology to analyse hybrid data collection from interviews, document and case studies in the course syllabus. The outcome of this research is a theoretical framework of contents that would aid critical dialogue in the subject of Islamic architecture. Materials of diverse context and problems facilitate learning, enabling students to construct an encompassing understanding of Islamic architecture.